Die ironie in enkele gedigte in Tristia van N P van Wyk Louw - Smuts, Susanna Elizabeth (Afrikaans and Netherlandic Studies, 2016)
This study is an investigation of the ironical attribute inherent in poems which appear in Tristia by N P van Wyk Louw. The thesis can be divided into two sections: the first is an attempt at describing and defining philosophical irony; while the second serves as an introduction to the method (principally Literary Semantic) applied in the in-depth analysis in Chapter 4. The first chapter is a brief description of the history of irony starting ,with Socratic irony. Chapter 2.1 gives an eclectic view of the metaphysical irony of Nietzsche and his view of art. Chapter 2.2 describes Soren Kierkegaard's concept of irony and his distinction between aesthetic and ethic irony. It should become apparent that the religious irony of Kierkegaard flows mainly from the counterdistinction of the human to the godlike. In Chapter 2.3 existential irony is defined with reference to Kierkegaard as father of existential irony. N P van Wyk Louw's statements on art and his philosophy is viewed in chapter 2.4 with reference to the theories of the above mentioned philosophers. Chapter 3 refers to the poem as a vehicle for various implication phenomena, and views irony as a specific implication phenomenon. This section uses as an analytical foundation J L Austin's Speech Act Semantics and F de Saussure's distinction of synchronic and diachronic linguistics. Some definitions of irony are evaluated. No alternative definition is provided but some assumptions are put forward on the function of irony as a form of implication. Chapter 4 comprises in-depth text analyses of selected poems in Tristia. The function of irony in these poems is investigated. Chapter 5 provides a general explanation for the use of irony in Tristia. Two vital poems in Tristia are looked at and it is concluded that poetry is the medium through which this poet identifies his ironical relationship to the universe.